Living-donor uterus transplantation: pre-, intra-, and postoperative parameters relevant to surgical success, pregnancy, and obstetrics with live births - Brucker, Sara; Strowitzki, Thomas; Ţăran, Florin-Andrei; Rall, Katharina; Schöller, Dorit; Hoopmann, Markus; Henes, Melanie; Guthoff, Martina; Heyne, Nils; Zipfel, Stephan; Schäffeler, Norbert; Bösmüller, Hans; et al. (Journal of Clinical Medicine, 2020)
Uterus transplantation (UTx) can provide a route to motherhood for women with Mayer–Rokitansky–Küster–Hauser syndrome (MRKHS), a congenital disorder characterized by uterovaginal aplasia, but with functional ovaries. Based on our four successful living-donor transplantations and two resulting births, this analysis presents parameters relevant to standardizing recipient/donor selection, UTx surgery, and postoperative treatment, and their implementation in routine settings. We descriptively analyzed prospectively collected observational data from our four uterus recipients, all with MRKHS, their living donors, and the two newborns born to two recipients, including 1-year postnatal follow-ups. Analysis included only living-donor/recipient pairs with completed donor/recipient surgery. Two recipients, both requiring ovarian restimulation under immunosuppression after missed pregnancy loss in one case and no pregnancy in the other, each delivered a healthy boy by cesarean section. We conclude that parameters crucial to successful transplantation, pregnancy, and childbirth include careful selection of donor/recipient pairs, donor organ quality, meticulous surgical technique, a multidisciplinary team approach, and comprehensive follow-up. Surgery duration and blood vessel selection await further optimization, as do the choice and duration of immunosuppression, which are crucial to timing the first embryo transfer. Data need to be collected in an international registry due to the low prevalence of MRKHS.
Gesehen am 15.12.2020